Methodologies for Foreign and Emerging Markets Selection (Journal of Business, Universidad del Pacífico (Lima, Peru), 2013)
The objective of this document is to assess if there is an interest among academics to confirm if the methodology usually applied to select and evaluate international markets is adequate in the case of the denominated emerging markets. In this sense, from the methodological point of view we have turned to a structured search of documentation in respect to two central topics; emerging markets (EMs) and selection methodologies for international markets (SMEs). The findings indicate of the existence of a consensus that highlights that emerging markets portray characteristics that differentiate them from developed markets, situation that generates both opportunities and threats that have to be considered for their evaluation. Also, we have found three research papers that indicate limitations in the selection methodologies usually applied when evaluating the potential of emerging markets, proposing adaptations to the existing methodologies. However, the empirical testing of these proposals is limited. Finally, we consider important to indicate that we have found a larger number of conceptual articles rather than empirical studies regarding this topic of international markets selection.
Keywords: Emerging markets; emerging economies; transition economies; international market information; international market selection